Emerging Mechanisms Underpinning Neurophysiological Impairments in C9ORF72 Repeat Expansion-Mediated Amyotrophic Lateral Sclerosis/Frontotemporal Dementia - Pasniceanu, Iris-Stefania; Atwal, Manpreet Singh; Souza, Cleide Dos Santos; Ferraiuolo, Laura; Livesey, Matthew R. (Frontiers in Cellular Neuroscience, 2021)
Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are characterized by degeneration of upper and lower motor neurons and neurons of the prefrontal cortex. The emergence of the C9ORF72 hexanucleotide repeat expansion mutation as the leading genetic cause of ALS and FTD has led to a progressive understanding of the multiple cellular pathways leading to neuronal degeneration. Disturbances in neuronal function represent a major subset of these mechanisms and because such functional perturbations precede degeneration, it is likely that impaired neuronal function in ALS/FTD plays an active role in pathogenesis. This is supported by the fact that ALS/FTD patients consistently present with neurophysiological impairments prior to any apparent degeneration. In this review we summarize how the discovery of the C9ORF72 repeat expansion mutation has contributed to the current understanding of neuronal dysfunction in ALS/FTD. Here, we discuss the impact of the repeat expansion on neuronal function in relation to intrinsic excitability, synaptic, network and ion channel properties, highlighting evidence of conserved and divergent pathophysiological impacts between cortical and motor neurons and the influence of non-neuronal cells. We further highlight the emerging association between these dysfunctional properties with molecular mechanisms of the C9ORF72 mutation that appear to include roles for both, haploinsufficiency of the C9ORF72 protein and aberrantly generated dipeptide repeat protein species. Finally, we suggest that relating key pathological observations in C9ORF72 repeat expansion ALS/FTD patients to the mechanistic impact of the C9ORF72 repeat expansion on neuronal function will lead to an improved understanding of how neurophysiological dysfunction impacts upon pathogenesis.